Spatial Apparent Electrical Conductivity of Paddy Soil as Indicator of Selected Soil Physical Properties - Mohamed, Mastura (2011)
Efficient and accurate methods of measuring within-field variations of soil physical properties are important in precision farming. Soil sensors that can collect data across the field will provide several advantages over traditional measurement methods that involve soil sample collection and laboratory analysis. The study on sensor-based measurement such as Veris 3100 and soil physical properties (soil particle distribution, dry bulk density, porosity, soil water retention, saturated hydraulic conductivity, soil organic matter and soil compaction (CI)) has been done. The main reason for the study is to determine whether the on-the-go sensor-based soil apparent electrical conductivity (ECa) can be used as an indicator of soil physical properties. The ECa sensor was pulled across 380 ha paddy fields in Sawah Sempadan, Tanjung Karang, Selangor, Malaysia. The sensor provides values of deep (ECad) and shallow ECa (ECas). The soil samples were taken from two depths, topsoil (0 to 15 cm) and subsoil layer (16 to 30cm). The readings of cone index values were taken by using cone penetrometer at the same point as the soil sampling locations. Most properties were found to have significant correlation with ECa, in Zone 3. The soil physical properties were found to have more significant correlation in topsoil compared to subsoil layer. At topsoil layer, estimated Ks, sand, clay and porosity were significantly correlated with ECad while only estimated Ks, sand and clay had significant correlation with ECas. At subsoil layer, sand, silt and clay had significant correlation with both ECad and ECas. Results show that the models for the topsoil can use shallow ECas as an indicator (constant) and deep ECa for subsoil layer. The analysis for soil CI was run by correlating the CI at 4 depths of soil with ECa and found ECad can be used as an indicator to determine the most compacted layer in the paddy field which had negative correlation with CI at depth 2 (13-26 cm) and had significance with ECad in mid range ECad (zone 2). The study show only moisture content at saturation (0 kPa) had significant positive correlation with ECa. So that, ECa can be used as an indicator to determine soil moisture content when the field is in saturation stage. The Paddy Soil Physical Properties Calculator (PSPPC) was developed to ease users in estimating soil physical properties based on ECa values. JavaScript language was used to develop the GUI and the results using the calculator in web base feature. Textural class, sand percentage, silt percentage, clay percentage, bulk density, soil organic matter and saturated hydraulic conductivity can be calculated. This application can help users to estimate values of soil physical properties based on easily derived values of ECa. This calculator is only recommended for the Sawah Sempadan area because the program was developed based on data taken in that area.